Professionalism in probation: making sense of marketisation - Tidmarsh, Matt (Routledge frontiers of criminal justice, 2021)
Probation: a profession in transition -- Probation's professional project -- Transforming rehabilitation: the micro-physics of (market) power -- 'Well, what are you?' Professionalism, identity, and culture in probation -- Probation practice, architecture, and an art of distributions -- Payment by results, 'penal accountancy', and the regulation of autonomous conduct -- 'The right kind of person for the job'? Professionalism, probation values, and emotional labour -- Beyond marketisation? The future of professionalism in probation.